Explore Westonci.ca, the top Q&A platform where your questions are answered by professionals and enthusiasts alike. Discover detailed solutions to your questions from a wide network of experts on our comprehensive Q&A platform. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.

What is the solution to −6x−4≥−2(x−4) ?

x≤−3

x≥3

x≥2

x≤−1


Sagot :

Answer:

The correct answer is: Option 1: x≤-3

Step-by-step explanation:

Given inequality is:

[tex]-6x-4\geq -2(x-4)[/tex]

First of all, we will distribute -2 into the bracket

[tex]-6x-4\geq -2x+8[/tex]

Then we will add 4 on both sides

[tex]-6x-4+4\geq -2x+8+4\\-6x \geq -2x+12[/tex]

Adding 2x on both sides

[tex]-6x+2x\geq -2x+12+2x\\-4x\geq 12[/tex]

Dividing both sides by 4

[tex]\frac{-4x}{4} \geq \frac{12}{4}\\-x \geq 3[/tex]

As there should be only x on the left side of the inequality we will multiply the inequality with -1.

Multiplying the inequality with -1 reverses the sign of inequality

So,

[tex]x \leq -3[/tex]

Hence,

The correct answer is: Option 1: x≤-3